PERLUKAH KRIMINALISASI TERHADAP PERILAKU AMORAL? PERDEBATAN PATRICK DEVLIN DAN H.L.A. HART - Petrus CKL Bello (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
The famous debate in the mid-20th century between Patrik Devlin and H.L.A. Hart about the relationship between law and morality in discussing the limits of criminal law in matters of individual behaviour that are considered contrary to public morality, a debate which was sparked by the Report of the Wolfenden Committee on Homosexual Offenses and Prostitution (The 1957 Report of the Wolfenden Committee on Homosexual Offense and Prostitution) for decriminalize private male homosexual activity. Although the focus of the initial debate was limited by the framework of the debate about criminal law in general and homosexual offenses in particular with the harm principle from John Stuart Mill to illustrate the sharp distinction between law and morality and a static conception of the relationship between the two, this article seeks to explore how Devlin developed the application of moral standards in areas of law other than criminal law. Regarding the debate between the two thinkers, the author will decontextualize the debate within the framework of enforcing Indonesian criminal law against sexually immoral behaviour.